2012
DOI: 10.1371/journal.pone.0044638
|View full text |Cite
|
Sign up to set email alerts
|

Improving Lambda Red Genome Engineering in Escherichia coli via Rational Removal of Endogenous Nucleases

Abstract: Lambda Red recombineering is a powerful technique for making targeted genetic changes in bacteria. However, many applications are limited by the frequency of recombination. Previous studies have suggested that endogenous nucleases may hinder recombination by degrading the exogenous DNA used for recombineering. In this work, we identify ExoVII as a nuclease which degrades the ends of single-stranded DNA (ssDNA) oligonucleotides and double-stranded DNA (dsDNA) cassettes. Removing this nuclease improves both reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(85 citation statements)
references
References 51 publications
2
83
0
Order By: Relevance
“…We expect that optimized protocols involving several cycles would produce results closer to those seen with Recβ in E. coli . Further, the P. putida EM42 cell factory, while purged of certain endonucleases (Martínez‐García et al ., 2014) that could inhibit strand displacement (Mosberg et al ., 2012), harbours a fully functional MMR system. As mentioned, MMR machinery is known to interfere with the MAGE platform in various bacterial species, dampening final rates of mutagenesis.…”
Section: Discussionmentioning
confidence: 99%
“…We expect that optimized protocols involving several cycles would produce results closer to those seen with Recβ in E. coli . Further, the P. putida EM42 cell factory, while purged of certain endonucleases (Martínez‐García et al ., 2014) that could inhibit strand displacement (Mosberg et al ., 2012), harbours a fully functional MMR system. As mentioned, MMR machinery is known to interfere with the MAGE platform in various bacterial species, dampening final rates of mutagenesis.…”
Section: Discussionmentioning
confidence: 99%
“…They found that the use of an E. coli strain deleted of four ssDNA exonucleases (RecJ, ExoI, ExoVII, and ExoX) resulted in higher amounts of mean allele conversions using the Co-MAGE protocol (374). The implication is that more oligos were surviving the threat of degradation by these exonucleases prior to being annealed to the replication fork.…”
Section: Mechanisms Of λ Red Recombineering Recombineering With Ssdnamentioning
confidence: 99%
“…E. coli degrades linear double-strand DNA very rapidly via the RecBCD and SbcCD exonucleases. Gam, one of the three proteins of , prevents the degradation of the linear DNA by inhibiting the nucleases, Exo generates single-stranded DNA, and Beta binds to this single-stranded DNA and facilitates recombination to homologous chromosomal regions (16). In Bacillus subtilis, such a system is not necessary.…”
mentioning
confidence: 99%